2022
DOI: 10.1021/acssuschemeng.2c02883
|View full text |Cite
|
Sign up to set email alerts
|

Direct Air Capture of CO2 via Ionic Liquids Derived from “Waste” Amino Acids

Abstract: Direct capture of CO 2 from anthropogenic emissions is an imperative societal task as the concentration of global atmospheric CO 2 continues to increase drastically. The longterm goal of negative emission requires methods to remove carbon directly from the atmosphere, oceanwater, and nonpoint sources. Ionic liquids (ILs) have had a pivotal impact on finding and implementing innovative solutions that enable a more sustainable future. Here, we report the first example of an IL-enabled approach for direct CO 2 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Their potential in DAC is based on their versatility to combine various cations and anions, which offers the possibility of fine-tuning the chemical and physical attributes of the absorbent. Furthermore, particularly given their low volatility, minimal corrosiveness, exceptional chemical and thermal stability, nonflammable nature, and reduced vapor pressure are key features for sustainable CO 2 capture process. , In addition, basic ILs can activate water molecules, forming a guest@host complex that can react with CO 2 to produce bicarbonate . This presents a significant advantage compared to other materials, as they can achieve a high sorption capacity even under humid conditions.…”
Section: Materials For Direct Air Capturementioning
confidence: 99%
“…Their potential in DAC is based on their versatility to combine various cations and anions, which offers the possibility of fine-tuning the chemical and physical attributes of the absorbent. Furthermore, particularly given their low volatility, minimal corrosiveness, exceptional chemical and thermal stability, nonflammable nature, and reduced vapor pressure are key features for sustainable CO 2 capture process. , In addition, basic ILs can activate water molecules, forming a guest@host complex that can react with CO 2 to produce bicarbonate . This presents a significant advantage compared to other materials, as they can achieve a high sorption capacity even under humid conditions.…”
Section: Materials For Direct Air Capturementioning
confidence: 99%
“…25−28 Such task-specific ionic liquids (TSILs) have demonstrated promising potential in DAC. 29,30 However, ILs suffer from high viscosity that impedes fast absorption rates of CO 2 and TSILs exhibit increase in viscosity upon CO 2 binding, limiting mass transport of CO 2 . 31 To overcome challenges associated with the viscosity and cost of TSILs, small molecule amines have been introduced to ILs for improved CO 2 absorption, providing both chemisorption pathways and low-volatility solvents for amines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…first reported a series of amino acid ILs (AAILs) with 20 natural amino acids as anions, which were prepared by neutralization between various onium hydroxides and amino acids. In the context of green and sustainable chemistry, AAILs offer greener alternatives to existing CO 2 -chemsorptive materials because amino acids are readily available from renewable sources in large quantities. The solubility and reaction mechanism of CO 2 in the resulting AAILs have been widely investigated by several research groups. In particular, AAILs with phosphonium cations and l -prolinate anion ([Pro] − ) show superior properties for CO 2 capture. Brennecke et al reported that a trihexyl­(tetradecyl)­phosphonium ([P 666,14 ] + )-type AAIL with [Pro] − as the anion can absorb CO 2 in a 1:1 stoichiometry of CO 2 /AAIL by stabilizing the carbamic acid moiety rather than through carbamate formation. , Matsuyama et al investigated various facilitated transport membranes using tetra- n -butylphosphonium ([P 4444 ] + )-based AAILs, and [P 4444 ]­[Pro] exhibited CO 2 permeability and CO 2 /N 2 selectivity considerably greater than the Robeson upper bounds under low CO 2 feed pressure conditions. , …”
Section: Introductionmentioning
confidence: 99%